Efficiency of chemical control of Brevipalpus phoenicis Geijskes, 1939 (Acari: Tenuipalpidae) in citrus when affected by simulated rainfall - Vegato, Luiz Gonzaga Chia; Nogueira, Carlos Eduardo Tozzi; Afférri, Flavio Sergio; Rando, Jael Simões Santos; Lima, Sérgio Luiz (Pesquisa Agropecuaria Brasileira, 1994)
The objective of this research was to test the control of Brevipalpus phoenicis (Geijskes, 1939) by the hexythiazox and quinometionato products in citrus crop with and without adhesive spread and when submited to artificial rain. The plants were sprayed at 2, 4, 8, 24 and 48 hours. When dried, the fruits were collected (eight/plants) and half of them were washed in laboratory with artificial rainfall on the basis of 30 mm/h during 15 minutes establishing the following treatments: T1 -hexythiazox + washing; T2 -hexythiazox + agral + washing; T3 - quinometionato + washing; T4 - quinometionato + agral + washing; T5 - control + agral + washing; T6 -hexythiazox; T7 - hexythiazox + agral; T8 - quinometionato; T9 - quinometionato + agral; T10 - control + agral. Thus, all the fruits were inoculated with ten females of B. phoenicis and five days later the mites alive were counted and eliminated. Approximately 15 days later the number of larvae alive were also counted. The results obtained allowed the following conclusions: a) the acaricides were efficient to control B. phoenicis; b) the rainfall (washing) did not alter the efficiency; c) the agral did not change the results.